Effect of ormeloxifene, a selective estrogen receptor modulator, on biomarkers of endometrial receptivity and pinopode development and its relation to fertility and infertility in Indian subjects - Makker, Annu; Tandon, Indu; Goel, Madhu Mati; Singh, Mastan; Singh, Man Mohan (Fertility and sterility, 2009)
To compare expression of endometrial estrogen (ER) and progesterone (PR) receptors, β 3-integrin subunit, leukemia inhibitory factor (LIF), interleukin-6 (IL-6), and pinopodes in Indian women using ormeloxifene as a contraceptive with fertile and infertile subjects during the window of implantation. Controlled, prospective, clinical study. Hospital-based reproductive health unit and research laboratories. Thirteen fertile women, 6 using ormeloxifene (30 mg/week), 29 with primary and 10 with secondary infertility. Transvaginal ultrasonography, midluteal endometrial biopsies, and blood samples. Histologic dating, endometrial thickness, immunohistochemical localization of ER, PR, β 3-integrin subunit, LIF, and IL-6 and scanning electron microscopy. Ormeloxifene significantly reduced endometrial thickness, pinopode density, and caused histologic delay with increased epithelial ER and PR and unaltered epithelial β 3-integrin subunit expression. Appearance of fully developed pinopodes, down-regulation of epithelial PR, and increased epithelial β 3-integrin subunit expression was observed in in-phase endometrium from fertile and infertile women. LIF and IL-6 expression and serum estradiol and progesterone levels remained unaltered between groups. Ormeloxifene-induced effects might produce asynchrony between endometrial and embryo development resulting in implantation failure. Based on unaltered luteal phase serum progesterone concentration, ormeloxifene did not appear to prevent ovulation in any participant.